PENGARUH PENGGUNAAN ALAT PERAGA PAPAN PECAHAN TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI PECAHAN SISWA KELAS IV SDN 13 SINGKAWANG - Maulana; Wahyuni Oktavia; Yogi Setya Novanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low mathematics learning outcomes of students in fractional materials caused by the use of less varied learning media and learning that is still teacher-centered. This study aims to determine the effect of the use of fractional board teaching aids on mathematics learning outcomes and responses of grade IV students of SDN 13 Singkawang. The research method used is experimental research with a pre-experimental design of the one group pretest-posttest type. The research population was all grade IV students with sampling techniques using total sampling. Data collection techniques include tests and questionnaires, while data analysis uses normality tests, homogeneity tests, and t-tests at a significance level of 5%. The results showed that there was a significant difference between learning outcomes before and after the use of fractional board props, indicated by the significance value (Sig. 2-tailed) of 0.000 < 0.05 so that an alternative hypothesis was accepted. In addition, students' responses to the use of props showed a very good category with a percentage of 91%. Thus, the use of fractional board teaching aids has a positive effect on improving mathematics learning outcomes in fractional materials and is able to increase student involvement in the learning process.